Optimization in design of hybrid electric power network using HOMER. (2021) - Balachander, K.; Suresh Kumaar, G.; Mathankumar, M.; Manjunathan, A.; Chinnapparaj, S.
Abstract: This research work proposes to refine the hybrid electrical power network to supply a single residence's electrical load located in Coimbatore, Tamilnadu. The load shape of the household is considered by the pattern of energy usage used and supplied for different electrical uses by the PV/Wind/Diesel Generator (DG) set. The simulation and optimization of the scheme is carried out by the Hybrid Optimization System for Electric Renewable (HOMER) model from the National Renewable Energy Laboratory (NREL). The various analyses were discussed like Net Present Value (NPV), Energy Expense, Energy Output, Usage, Excess Energy generated by individual components of the system and the pollution produced.